Engaging with omnichannel brands: the role of consumer empowerment - Itani, Omar S. (2023)
Purpose This study aims to integrate brand and retailer levels variables to examine the direct and indirect relationships between omnichannel retailing and consumer engagement. Design/methodology/approach Survey data are collected from a sample consumers of different omnichannel retailing brands operating in the skin care industry. Partial least squares structural equation modeling is utilized. Findings The study finds brand channels' integrated interactions (process and content consistency) to increase consumer brand engagement. Findings show retailer consumer empowerment to intensify the impact of omnichannel retailing on consumer engagement. Results also show brand channels' integrated interactions to increase consumer brand familiarity, which mediates the effect of omnichannel retailing on consumer engagement. Originality/value This study suggests that integrating brand- and retailer-level variables is vital to understand the effect of omnichannel retailing on consumer engagement. The study concludes that for successful omnichannel strategy, collaboration between brands and retailers is imperative.